A novel cuproptosis-related lncRNA nomogram to improve the prognosis prediction of gastric cancer - Feng, Anqi; He, Lingnan; Chen, Tao; Xu, Meidong (Frontiers in Oncology, 2022)
Background: Cuproptosis is a copper-triggered modality of mitochondrial cell death and cuproptosis process may play important roles in gastric cancer development. However, little is known about cuproptosis-related lncRNAs in gastric adenocarcinoma (STAD). This study is aimed to investigate the potential prognostic signatures of cuproptosis-related lncRNAs in STAD. Methods: The Cancer Genome Atlas (TCGA) database was used to obtain gene expression profiles, clinicopathological and OS information for STAD. Cuproptosis-related genes were collected based on previous studies and cuproptosis-related lncRNAs were screened out by co-expression analysis. The nomogram constructed by Cox regression analysis with the minimum absolute contraction and selection operator (lasso) algorithm. In addition, the potential response of ICB therapy and immune evasion incidence were estimated with Tumor Immune Dysfunction and Exclusion (TIDE) algorithm. The correlation of immune checkpoint CD209 and HAVCR2 expressions associated with risk scores were experimentally testified by RT-qPCR, Western Blot and IHC. Results: Patients were classified into high-risk and low-risk groups based on the risk score calculated in this model. The Kaplan-Meier survival curve analysis revealed the high-risk group was associated with poor prognosis. Multivariate Cox regression analysis suggested that this lncRNA prediction model was an independent risk factor affecting the OS rate. Furthermore, ROC curve indicates that the nomogram was superior to traditional clinicopathological features in predicting STAD prognosis. Finally, functional enrichment analysis and immune checkpoint investigation revealed that the nomogram is notably associated with immune functions, RT-qPCR and Western Blotting demonstrated the co-expression relationship of LINC01150 with CD209 and HAVCR2. Conclusion: A novel cuproptosis-related lncRNAs signature impacts on the prognosis and immunological features of GC.